2004
DOI: 10.1021/nl035010n
|View full text |Cite
|
Sign up to set email alerts
|

Superparamagnetic Fe2O3 Beads−CdSe/ZnS Quantum Dots Core−Shell Nanocomposite Particles for Cell Separation

Abstract: This paper describes the synthesis of new nanocomposite nanoparticles that consist of polymer coated γ-Fe2O3 superparamagnetic cores and CdSe/ZnS quantum dots (QDs) shell. A single layer of QDs was bound to the surface of thiol-modified magnetic beads through the formation of thiol−metal bonds to form luminescent/magnetic nanocomposite particles. Transmission electron microscopy (TEM) and energy disperse spectroscopy (EDS) were used to characterize the size, size distribution, and composition of the luminescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
363
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 596 publications
(366 citation statements)
references
References 24 publications
3
363
0
Order By: Relevance
“…On the other hand, filtration might be applied to removing those chemical pollutants, but the sample process afterwards requires the extraction step, which could result in damages of bacterial cells. A magnetic nanoparticle based method has been shown successful in separating cancer cells from serum samples, and it was suggested that such a method could be used in separating bacteria from complex system as well [28]. Use of antibody-coated magnetic particles could extract bacteria from the liquid suspensions, thus concentrating the species and minimizing the influence of the dissolved chemical ions on the technology developed here.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, filtration might be applied to removing those chemical pollutants, but the sample process afterwards requires the extraction step, which could result in damages of bacterial cells. A magnetic nanoparticle based method has been shown successful in separating cancer cells from serum samples, and it was suggested that such a method could be used in separating bacteria from complex system as well [28]. Use of antibody-coated magnetic particles could extract bacteria from the liquid suspensions, thus concentrating the species and minimizing the influence of the dissolved chemical ions on the technology developed here.…”
Section: Resultsmentioning
confidence: 99%
“…The extended x-ray absorption fine structure (EXAFS) spectra were analyzed according to standard procedures and the spectra were normalized to the absorption coefficient averaged at high energy in order to eliminate the dependence of absorption with the sample thickness. 5 Two kind of magnetic measurements were performed combining SQUID and a Quantum Design PPMS magnetometer with the vibrating-sample (VSM) option: (i) after a zero field cooling (ZFC) from 300 K down to 10 K, it was measured the variation of the magnetization as a function 10 of the temperature between 10 and 340 K, M ZFC (T), and after field cooling (FC), M FC (T). In both cases the applied magnetic field was fixed to H = 10 Oe.…”
Section: Methodsmentioning
confidence: 99%
“…We attempted to magnetically modulate the complexes with a 0.02 T solenoid system, but the magnetic force was not sufficient to overcome Brownian motion, as the magnetic force exerted on a particle is proportional to the volume of the magnetic component. 26 Recent reports showed that CdSe quantum dots encapsulating a ∼10 nm magnetic core had a ∼70% lower emission quantum yield 46 and a ∼90% shorter lifetime 45 than the original quantum dots. In contrast, the optical properties of SWNT in this study are not significantly affected by the presence of the iron oxide nanoparticles.…”
mentioning
confidence: 99%